Devils of the Digital Era: Tetheredness to Technology and Mental Health in The Context of The Workplace - Anwar, Farooq; Iqbal, Zanaiara (International Journal of Membrane Science and Technology, 2023)
Advancement in communication technology arrivals has made workplaces easy to connect to their employees in off-working hours. However, there is a growing concern in local and global organizations regarding workplace connectivity in off-working time. After office hours, connectivity to the workforce increases due to the flexible use of technology such as smartphones, laptops, and other portable devices. Previous studies regarding psychological health allude that employees’ mental health is at higher risk while using smartphones in off-job hours due to emails, phone calls, texts, and other phone-related engagements. This study examines the relationship between tetheredness to technology on mental health through mediating role of sleep deprivation and moderating role of work to family conflict. We conducted an empirical study which consists of 255 IT Managers who filled out questionnaires to test the hypothesized influences by calculating correlation and regression through process macro. The findings showed that Tetheredness to technology has negatively correlated with mental health, sleep deprivation, and work to family conflicts. This study also discloses moderated mediation; the indirect effect of Tetheredness to technology on mental health through sleep deprivation is stronger for employees who have faced higher work to family conflicts. The results have practical implications for public and private IT-based organizations whose workforce has experienced off-working hours connectivity related to job stressors like 24/7 hours connectivity demands and job insecurity.